Constituents of Political Theory : Selected Articles of the Warsaw School of Political Theory. - Burzyński, Jan. (Studies in Politics, Security and Society Series, 2021)
The book presents a collection of articles authored by several members of the Warsaw School of Political Theory, affiliated with the University of Warsaw. The team of scholars, first founded in the 1970s by professor Artur Bodnar, has been conducting research under the leadership of professor Mirosław Karwat.